2020
DOI: 10.1096/fba.2019-00032
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of the unfolded protein response increases RANKL expression

Abstract: Increased production of the osteoclastogenic cytokine RANKL is a common feature of pathologic bone loss, but the underlying cause of this increase is poorly understood. The unfolded protein response (UPR) is activated in response to accumulation of misfolded proteins in the endoplasmic reticulum (ER). Failure to resolve misfolding results in excess UPR signaling that stimulates cytokine production and cell death. We therefore investigated whether RANKL is one of the cytokines stimulated in response to elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…DNA damage and ER stress stimulate the production of the proresorptive cytokine receptor activator of NF‐κB ligand (RANKL) 31–33 . Stimulation of RANKL by these cellular stressors is thought to contribute to the increase in bone resorption and thereby contribute to bone loss in pathological conditions associated with elevated DNA damage 33 and ER stress 31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA damage and ER stress stimulate the production of the proresorptive cytokine receptor activator of NF‐κB ligand (RANKL) 31–33 . Stimulation of RANKL by these cellular stressors is thought to contribute to the increase in bone resorption and thereby contribute to bone loss in pathological conditions associated with elevated DNA damage 33 and ER stress 31 .…”
Section: Resultsmentioning
confidence: 99%
“…DNA damage and ER stress stimulate the production of the proresorptive cytokine receptor activator of NF‐κB ligand (RANKL). 31 , 32 , 33 Stimulation of RANKL by these cellular stressors is thought to contribute to the increase in bone resorption and thereby contribute to bone loss in pathological conditions associated with elevated DNA damage 33 and ER stress. 31 We have previously shown that CMA deficiency causes an increase in Rankl ( Tnfsf11) mRNA levels in vitro and in vivo 15 ; however, whether CMA influences DNA‐damage‐ or ER stress‐ induced elevation of RANKL is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UPR increased the expression of RANKL in osteoblasts and osteocytes, thus indirectly promoting osteoclast formation and bone resorption [125]. The IRE1-XBP1 signaling pathway activated parathyroid hormone receptor-1 (PTH1R) transcription in osteoblasts, and PTH (parathyroid hormone)/PTH-related peptide promoted RANKL expression in osteoblasts via PTH1R, thereby promoting osteoclast differentiation [15].…”
Section: Upr and The Expression Of Rankl In Osteoblastsmentioning
confidence: 99%
“…Besides, the calcium signaling also control the growth and differentiation of BMSCs, and related downstream signaling pathways can be activated through the release of Ca 2+ from endoplasmic reticulum to elicit its regulatory effects on BMSCs differentiation [ 31 ]. During the ER stress, the efflux of Ca 2+ from endoplasmic reticulum would function as an important regulative signaling on the cellular behaviors, and the UPR induced by ER stress also could promote the RANKL expression in primary osteoblastic progenitors [ 32 ]. All the previous reports suggest some potential correlations among the ER stress, osteoblastogenesis and osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%